The Initiatives of Local Government Units (LGUs) in Batangas on Climate Change - Jennifer G. Manalo (Philippine Association of Institutions for Research, Inc., 2018)
The local government units in the Philippines are at the forefront of disaster management including responding to the impacts of climate change. With the necessity to address this problem, this study aimed to determine the initiatives of the local government units (LGUs) in Batangas on climate change. The study made use of descriptive research which involved quantitative and qualitative methods in gathering data. Research triangulation was used. The subjects of the study were the Disaster Risk Reduction Management and planning officers of three component cities and twenty-seven municipalities of Batangas. Frequency counts, percentages, and average weighted mean were used in the statistical analysis of data. Results of the study revealed that LGUs in Batangas comply with the provisions of Republic Act No. 10121, otherwise known as Philippine Disaster Risk Reduction and Management Act of 2010. LGUs to organize disaster risk reduction and management councils at the local level. Likewise, cities and municipalities of Batangas implement policies through local ordinances to adopt and strengthen RA 9003. They are implementing initiatives that encourage businesses to promote climate-smart services and practices. Assessment of farming practices, extension services and linkages with GOs, NGOs and other agencies in the implementation of climate change initiatives needs to be improved.